Neuroprotective Role of the PI3 Kinase/Akt Signaling Pathway in Zebrafish - Chen, Shuang; Liu, Yunzhang; Rong, Xiaozhi; Li, Yun; Zhou, Jianfeng; Lu, Ling (Frontiers in Endocrinology, 2017)
Neuronal survival and growth in the embryo is controlled partly by trophic factors. For most trophic factors (such as Insulin like growth factor-1, IGF1), the ability to regulate cell survival has been attributed to the PI3K/Akt kinase cascade. This study presents data illustrating the role of PI3K/Akt in attainment of normal brain size during zebrafish embryogenesis. Blocking PI3K with inhibitor LY294002 caused a significant reduction in brain size (in addition to global growth retardation) during zebrafish embryogenesis. This PI3 Kinase inhibition-induced brain size decrease was recovered by the overexpression of Myr-Akt, a constitutive form of Akt. Further analysis reveals that expressing exogenous Myr-Akt significantly augmented brain size. Whole mount in situ hybridization analysis of several marker genes showed that Myr-Akt overexpression did not alter brain patterning. Furthermore, the expression of Myr-Akt was found to protect neuronal cells from apoptosis induced by heat shock and UV light, suggesting that inhibition of neuronal cell death may be part of the underlying cause of the increased brain size. These data provide a foundation for addressing the role of PI3K/Akt in brain growth during zebrafish embryogenesis.